Anaerobic capacity may not be determined by critical power model in elite table tennis players - Zagatto, Alessandro Moura [UNESP]; Papoti, Marcelo [UNESP]; Gobatto, Claudio Alexandre [UNESP] (My University, 2008)
The aim of the present study was to verify the applicability of anaerobic work capacity (AWC) determined from the critical power model in elite table tennis players. Eight male international level table tennis players participated in the study. The tests undertaken were: 1) A critical frequency test used to determinate the anaerobic work capacity; 2) Wingate tests were performed using leg and arm ergometers. AWC corresponded to 99.5 ± 29.1 table tennis balls. AWC was not related to peak (r = -0.25), mean (r = -0.02), relative peak (r = -0.49) or relative mean power (r = 0.01), nor fatigue index (r = -0.52) (Wingate leg ergometer). Similar correlations for peak (r = -0.34), mean (r = -0.04), relative peak (r = -0.49), relative mean power (r = -0.14) and peak blood lactate concentration (r = -0.08) were determined in the Wingate arm ergometer test. Based on these results the AWC determined by a modified critical power test was not a good index for measurement of anaerobic capacity in table tennis players. ©Journal of Sports Science and Medicine (2008).
Keywords: Anaerobic capacity; Critical frequency; Lactate; Table tennis; Wingate test